Making the case for creative spaces in Australian libraries. Issue 1 (2nd January 2016) - Boyle, Emily; Collins, Michelle; Kinsey, Robyn; Noonan, Clare; Pocock, Andrew
Abstract: The establishment of creative spaces (any place where the community can come together for informal and shared social learning) in public libraries has been an emerging trend worldwide in recent years. It is timely to examine what this means for Australian libraries and their communities, and how such spaces can be successfully established. This article, based on a toolkit produced for a Public Libraries Victoria Network and State Library Victoria Shared Leadership project, provides an overview of what creative spaces are, why they are relevant to libraries and the benefits they can bring to libraries and their communities. It also draws on literature from the field to summarise some key best practice principles for developing a creative space. It reiterates the findings of other commentators in recommending that creative spaces be included in Australian library offerings because of their clear strategic fit, community benefits and scalability for different libraries. These spaces, and their activities, equipment and funding models vary widely, but it is clear that successful creative spaces share certain qualities. There are many clear benefits to both libraries and their communities from having a creative space. These include empowering your community, fostering community collaboration and co-creation, growing a larger, more engaged user base, enabling inter-generational learning and social connectedness, facilitating trans-literacy, developing a culture of lifelong learning and adding socio-economic advantage to communities. Creative spaces also provide an opportunity for libraries to future-proof themselves and adapt to meet the changing nature of society.